Co‐Location Synergies: Specialised Versus Diverse Logistics Concentration Areas. (6th July 2015) - van den Heuvel, Frank; van Donselaar, Karel; de Langen, Peter; Fransoo, Jan
ABSTRACT: Although anecdotal evidence suggests that co‐location can bring about several benefits for co‐located logistics companies, implying the need to incorporate such considerations in location decisions, these benefits have hardly been analysed empirically. This paper provides detailed insights for decision making by precisely analysing the synergies attained through the co‐location of logistics firms in specialised and diverse logistics concentration areas. The paper analyses whether co‐location in logistics concentration areas that specialise in fresh produce provides additional benefits over co‐location in diverse logistics concentration areas that do not specialise in any particular type of products. A survey of managers of 127 logistics firms located in logistics concentration areas tested for differences in synergies through co‐location in specialised versus diverse logistics concentration areas. Logistics firms co‐located in fresh produce logistics parks share knowledge, combine transport and storage capacities, and trade products more than logistics firms co‐located in diverse logistics concentration areas.